The Effect of Education Through Video on the Knowledge, Attitudes, and Skills about Foot Care in Type 2 Diabetes Mellitus Patients - Fathoni, Akhmad; Sentana, Aan Dwi; Emilyani, Desty; Cembun, Cembun; Lestari, Vira Ayu (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2024)
Diabetes mellitus can cause various complications, one of which is diabetic foot ulcers. Improper management of foot ulcers results in rapid and widespread infection. This will result in amputation. Foot care is an effort to avoid disturbances in the feet so as to minimize amputation. The purpose of this study was to determine whether there is an effect of foot care education through videos on knowledge, attitudes, and skills in patients with type 2 diabetes mellitus. The research method used a pre-experimental design with a one group pretest - posttest approach. The sample was 68 patients with type 2 diabetes mellitus in the working area of the Mangkung Health Center in 2023 who were taken by simple random sampling technique. Data collection using a questionnaire and then analyzed with the Wilcoxon test. The results of the study before education were obtained most had poor knowledge as many as 64 respondents (94.1%), low attitudes 68 respondents (100%), and lack of skills 68 respondents (100%). After education, most of them had good knowledge 46 respondents (67.6%), high attitudes 65 respondents (95.6%), and good skills 61 respondents (89.7%). Statistical test results show the value of knowledge, attitudes, and skills obtained Ï value 0.001 < É‘ = 0.05. It can be concluded that there is an effect of foot care education through video on knowledge, attitudes, and skills.